Calibrating and Bootstrapping Modal Judgment. - Carbonell, Felipe Morales (Disputatio: International Journal of Philosophy, 2023)
In this paper, I consider the question of whether calibration is required for modalizing mechanisms to be reliable, that is, whether it is necessary for modalizing mechanisms to be adjusted to prevent overgeneration and undergeneration of modal beliefs. I first argue that the calibration requirement affects differently what I call bootstrapping and ordinary cases. Identifying different ways in which a modalizing mechanism could be calibrated, I argue that not all of them are effective or even viable in bootstrapping cases. Then, by taking a diachronic perspective, I offer a simplified account of how different calibration mechanisms can be bootstrapped, with an emphasis on the social dimension of modal judgment.